Effect of Deflector Plate for Particle Size Segregation Control - Kang-Min Kim; Ju-Hun Kim; Jae-Hong Kwon; Ji-A Lee; Jeong-Whan Han (Archives of Metallurgy and Materials, 2019)
In general, uniform mixing of particles is desirable in the process of particle handling. However, during the charging of sinter feed and upper ore, size segregation must be induced to prevent heat imbalance, ensure bed permeability, and prevent the loss of fine ore. In this study, upper ore charging was simulated using a discrete element method (DEM) to find the optimal method for controlling particle size segregation, and the segregation characteristics in the upper ore bed were investigated when a deflector plate was applied to the charging machine. The degree of vertical segregation increased when a deflector plate was applied, and it was confirmed that the segregation direction in the upper ore bed can be controlled by adjusting the charging direction of the upper ore by using a deflector plate. In order to apply this method directly to the actual process, further study is needed to understand the influence of the characteristics of the deflector plate such as length and angle.